Pillar depicting a four-armed Parvati holding a kamandalu and a mala - Temples of India Project Team (Jio Institute, 2024)
The pillars in the mandapa of the Harshnath Temple lack homogeneity and may have been a later replacement. One of them is enriched with beautiful images of apsaras and female deities like Parvati, as seen in this image, within the niches of the pillar. Under these pillar niches are panels depicting musicians, dancers, celestial beings, deities such as Ganesha and ascetics. These Shaiva ascetics align with the overall Shaiva theme of the temple. The image also depicts an ascetic worshipping the shivalinga. A four-armed Parvati is depicted holding a kamaṇdalu and mala in her lower hands and likely flowers in the upper two hands. Flanking her on both sides are attendant dwarfs. Below this scene, an ascetic with long matted hairs is shown in deep adoration to Shiva.